Advances in our understanding of anti-PF4 related immunothrombosis - Müller, Luisa; Gebicka, Patrycja; Handtke, Stefan; Schönborn, Linda; Thiele, Thomas (Frontiers in Immunology, 2026)
This article focuses on the central role of antibodies against platelet factor 4 (PF4) in mediating immunothrombosis, from classical heparin-induced thrombocytopenia (HIT) to vaccine-induced immune thrombocytopenia and thrombosis (VITT). The latter condition gained international attention during the rollout of vaccines against SARS-CoV-2. Since then, an increased awareness for anti-PF4 mediated disorders arose and patients were recognized with anti-PF4 disorders occurring without prior heparin or adenoviral vector vaccine exposure. These disorders include various acute and chronic VITT-like conditions, i.e. post-viral VITT, diaplacentally transmitted anti-PF4 antibodies in neonatal stroke, monoclonal gammopathies of thrombotic significance (MGTS) and chronic autoimmune VITT of unknown origin. All anti-PF4 related disorders share key serological and immunopathological features with VITT, such as the formation of immune complexes and platelet activation via the Fcγ receptor IIA (FcγRIIA). Via their activation, platelets form procoagulant, aggregatory and secretory phenotypes shaping their interplay with neutrophils, monocytes, and coagulation factors to amplify thrombotic responses. Integrating recent mechanistic insights, clinical observations and diagnostic developments, this review proposes an updated conceptual framework for anti PF4-related immunothrombosis. We aim to raise awareness among clinicians and researchers, to promote early diagnosis and encourage further translational research towards improved therapeutic strategies in this clinically significant area.